To cool or not to cool: understanding and improving cooling centre use in metro vancouver through community-based participatory action research - Liv Yoon; Giulia Belotti; Rachel Stern; Katherine White; Aida Mohajeri; Abby Zhou; Eduardo Rosales Miranda; Erika Siao; Thanh Le; Jeff Masuda; Eun-young Lee; Chris Buse (Environmental Research: Health)
Extreme heat events present significant health risks, particularly for populations facing systemic marginalization. Through interviews and FGs with 63 ( n = 60 residents; n = 3 service providers (SP)) participants, this paper explores the barriers and opportunities related to access and use of cooling centres from both user and provider perspectives, as well as broader implications for addressing vulnerability to extreme heat in the metro Vancouver region of British Columbia, Canada. Initially focused on cooling centres, our research expanded to include the complexities of individual and systemic responses to heat, highlighting the complex interplay between personal preferences and structural barriers. Key barriers to cooling centre usage reported by participants included concerns over safety, hygiene, stigma, lack of information, and infrastructural challenges such as transportation. SPs faced constraints with staffing, limited hours, and underutilization of additional services. Tensions emerged between individual, do-it-yourself (DIY) approaches and collective solutions, with participants seeking agency in their choices while acknowledging the need for improved, community-based interventions. The study also uncovered the unintended effects of inclusivity, as the presence of individuals who use substances or are unhoused in cooling spaces deterred some potential users, underscoring the challenges of designing universally accessible services. Broader systemic issues, such as housing security and the quality of indoor environments, further intersected with vulnerability to extreme heat, exacerbating risks for those opting to stay at home. The paper recommends leveraging existing public spaces, enhancing social networks, improving tenant protections, and fostering ‘right to cool’ initiatives to balance immediate relief with long-term systemic reform, particularly around the rental housing crisis and tenant insecurity. By addressing both individual and collective needs, this approach can mitigate the health impacts of extreme heat while promoting greater equity and resilience.